Improving the objectivity of the current World Para Swimming motor coordination test for swimmers with hypertonia, ataxia and athetosis using measures of movement smoothness, rhythm and accuracy - Maia, A. C.; Hogarth, L.; Burkett, B.; Payton, C. (Journal of Sports Sciences, 2021)
The current protocol for classifying Para swimmers with hypertonia, ataxia and athetosis involves a physical assessment where the individual`s ability to coordinate their limbs is scored by subjective clinical judgment. The lack of objective measurement renders the current test unsuitable for evidence-based classification. This study evaluated a revised version of the Para swimming assessment for motor coordination, incorporating practical, objective measures of movement smoothness, rhythm error and accuracy. Nineteen Para athletes with hypertonia and 19 non-disabled participants performed 30 s trials of bilateral alternating shoulder flexion-extension at 30 bpm and 120 bpm. Accelerometry was used to quantify movement smoothness; rhythm error and accuracy were obtained from video. Para athletes presented significantly less smooth movement and higher rhythm error than the non-disabled participants (p < 0.05). Random forest algorithm successfully classified 89% of participants with hypertonia during out-of-bag predictions. The most important predictors in classifying participants were movement smoothness at both movement speeds, and rhythm error at 120 bpm. Our results suggest objective measures of movement smoothness and rhythm error included in the current motor coordination test protocols can be used to infer impairment in Para swimmers with hypertonia. Further research is merited to establish the relationship of these measures with swimming performance.